Effect of splenectomy on platelet activation and decompression sickness outcome in a rat model of decompression - Lambrechts, K.; Pontier, J.; Mazur, A.; Buzzacott, Peter; Goanvec, C.; Wang, Q.; Theron, M.; Belhomme, M.; Guerrero, F. (2014)
© 2014, South Pacific Underwater Medicine Society. All rights reserved. Introduction: Splenic platelets have been recognized to have a greater prothrombotic potential than others platelets. We studied whether platelets released by splenic contraction could influence the severity and outcome of decompression sickness (DCS) and bubble-induced platelet activation. Methods: Sixteen, male Sprague-Dawley rats were randomly assigned to either a control or a splenectomized group. Both groups were compressed to 1,000 kPa (90 metres’ sea water) for 45 min while breathing air before staged decompression (5 min at 200 kPa, 5 min at 160 kPa and 10 min at 130 kPa). The onset time of DCS symptoms and of death were recorded during a 60-min observation period post dive. Parameters measured were platelet factor 4 (PF4) for platelet activation, thiobarbituric acid reactive substances (TBARS) for oxidative stress status and Von Willebrand factor (VWf) for endothelial activation. Results: There were no differences between the groups in DCS outcome or in PF4, TBARS and VWf concentrations. Conclusion: These results do not support that the spleen and its exchangeable platelet pool is involved in DCS pathogenesis in a rat model, invalidating the hypothesis that increased decompression-induced platelet aggregation could be influenced by splenic contraction and then play a role in DCS outcome.